A complete response to capecitabine and oxaliplatin chemotherapy in primary duodenal carcinoma with liver and nodal metastases: a case report - Seita Hagihara; Tetsunosuke Shimizu; Yoshihiro Inoue; Mitsuhiro Asakuma; Fumitoshi Hirokawa; Kohei Taniguchi; Michihiro Hayashi; Kazuhisa Uchiyama (Surgical Case Reports, 2018)
Abstract Background Primary duodenal adenocarcinoma (PDC) is a rare and lethal disease, and cases with nodal or distant metastasis have a poor prognosis. There are several reports of unresectable duodenal adenocarcinoma responding to systemic chemotherapy. However, there is little data on conversion surgery for PDC with distant metastasis. Case presentation We report a 55-year-old man with unresectable PDC with liver and nodal metastases responding to systemic chemotherapy with capecitabine and oxaliplatin (XELOX). His metastatic lesions completely disappeared by 18-fluorodeoxyglucose positron emission tomography/computed tomography after six courses of XELOX. Then, he underwent pancreaticoduodenectomy with lymph node dissection and partial resection of the liver. Postoperatively, the histological effect was determined to be grade 3, and the patient was diagnosed as having achieved pathological complete response (pCR). He is disease-free with no evidence of metastatic lesion for 14 months after surgery. Conversion surgery allowed R0 resection for unresectable PDC, and pCR can be achieved with XELOX treatment. Conclusion To the best of our knowledge, this case is the first report of conversion surgery for unresectable PDC with liver and para-aortic lymph node metastases.